1997
DOI: 10.1073/pnas.94.14.7531
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of NF-κB is increased in dopaminergic neurons of patients with Parkinson disease

Abstract: Evidence from postmortem studies suggest an involvement of oxidative stress in the degeneration of dopaminergic neurons in Parkinson disease (PD) that have recently been shown to die by apoptosis, but the relationship between oxidative stress and apoptosis has not yet been elucidated. Activation of the transcription factor NF-B is associated with oxidative stress-induced apoptosis in several nonneuronal in vitro models. To investigate whether it may play a role in PD, we looked for the translocation of NF-B fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
402
1
5

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 650 publications
(428 citation statements)
references
References 36 publications
(24 reference statements)
17
402
1
5
Order By: Relevance
“…Serum deprivation increased endogenous ceramide levels in a two-peak manner: the first peak occurred very rapidly within the first hour and the second peak at 16 h after the apoptotic process had already been engaged. These data, together with the previous findings which demonstrate that a 6-h pulse of c 2 -ceramide treatment is sufficient to commit neurons to die (Hunot et al, 1997), suggest that the first ceramide peak could be responsible for apoptosis induction. This rapid and transient increase of ceramide may reflect an activation of sphingomyelinases, as seen after stimulation of non-neuronal cells with TNF-␣, Il-1␤ and Fas-ligand (for review see Kronke, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Serum deprivation increased endogenous ceramide levels in a two-peak manner: the first peak occurred very rapidly within the first hour and the second peak at 16 h after the apoptotic process had already been engaged. These data, together with the previous findings which demonstrate that a 6-h pulse of c 2 -ceramide treatment is sufficient to commit neurons to die (Hunot et al, 1997), suggest that the first ceramide peak could be responsible for apoptosis induction. This rapid and transient increase of ceramide may reflect an activation of sphingomyelinases, as seen after stimulation of non-neuronal cells with TNF-␣, Il-1␤ and Fas-ligand (for review see Kronke, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, induction of apoptosis has been correlated to NF-kB activation in a wide variety of systems including fibroblasts, 26,27 T cells, 28,29 ceramide-activated osteoblasts 30 and dopaminergic neurons derived from Parkinson's disease patients. 31 Cell fate towards apoptosis or survival after NF-kB activation seems to be cell type specific and/or dependent on cell environment. In NIH3T3 cells, we demonstrated that NF-kB is proapoptotic as cell treatment with NF-kB inhibitors decreased executioner caspase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that inappropriate regulation of NF-kB/Rel-mediated transcription is associated with pathological conditions including acute inflammatory responses, toxic/septic shock, acute phase reactions, atherosclerosis, radiation damage, and also with several neuropathologies (Grilli et al, 1993;Baldwin, 1996;O'Neill and Kaltschmidt, 1997). In post-mortem tissue from patients with neurodegenerative disease or cultured Expression profiling of NMDA receptor antagonists in brain M Marvanová et al neurons exposed to neurotoxic stimuli, increased NF-kB activity in cells has been reported (Kaltschmidt et al, 1995;Terai et al, 1996;Hunot et al, 1997). Furthermore, several studies have demonstrated that stimulation of both NMDA and non-NMDA glutamate receptors strongly stimulate NF-kB in vitro (Guerrini et al, 1995;Kaltschmidt et al, 1995).…”
Section: Discussionmentioning
confidence: 99%